ANALISIS YURIDIS PEMEGANG HAK GUNA BANGUNAN YANG TELAH DALUWARSA - GEDE TUSAN ARDIKA; TITIN TITAWATI; RAMLI RAMLI (GANEC SWARA, 2021)
This study aims to analyze and examine how the consequences and legal remedies for holders of Building Use Rights that have expired in terms of PP no. 40 of 1996 concerning Cultivation Rights, Building Use Rights and Land Use Rights. This research uses a normative-empirical research method, with the statute approach, conceptual approach, case analysis approach and facts approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Field data collection using interview techniques and then analyzed qualitatively.The results of the study show that: 1) The legal consequences for the holders of Building Use Rights that have expired or have expired, in order to remain as the holders of Building Use Rights can be done in two ways, first through the extension of rights and secondly by renewal of rights. 2) Legal remedies against holders of Building Use Rights whose validity period has expired are through administrative measures, namely increasing the rights to property rights and legal remedies through the decisions of the State Administrative Court